2014
DOI: 10.5152/akd.2014.4950
|View full text |Cite
|
Sign up to set email alerts
|

Circulating matrix metalloproteinases and tissue inhibitors of metalloproteinases levels in pediatric patients with congenital heart disease: Relationship to cardiac functions

Abstract: Objective: The pathological effects of matrix metalloproteinases and their tissue inhibitors in cardiovascular diseases are of considerable interest. In our study, we aimed to determine and evaluate the potential significance of circulating matrix metalloproteinases-2 and 9, tissue inhibitors of matrix metalloproteinases-1 and 2 levels in four patient subgroup of pediatric cardiology field and expose pathophysiologic differences between these groups. Methods: Eighty-seven patients with the diagnosis of congeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…A study by Cheng et al in pediatric population showed a significant increase in serum level of MMP2 in CHD children with VSD compared to the control group, with a p < 0.01 [16]. Another study by Kihc et al on pediatric population with CHD showed that there was no significant increase in serum level of MMP in the cyanotic CHD group compared to the control group [17]. A study by Yamazaki et al in adult population showed that the serum level of MMP2 was significantly higher in patients with severe heart failure than in patients with mild heart failure, with a p < 0.01 [18].…”
Section: Discussionmentioning
confidence: 96%
“…A study by Cheng et al in pediatric population showed a significant increase in serum level of MMP2 in CHD children with VSD compared to the control group, with a p < 0.01 [16]. Another study by Kihc et al on pediatric population with CHD showed that there was no significant increase in serum level of MMP in the cyanotic CHD group compared to the control group [17]. A study by Yamazaki et al in adult population showed that the serum level of MMP2 was significantly higher in patients with severe heart failure than in patients with mild heart failure, with a p < 0.01 [18].…”
Section: Discussionmentioning
confidence: 96%
“…31 Furthermore, other biomarkers of collagen and other matrix metalloproteinase subtypes have been related to outcomes in congenital heart disease. [32][33][34] However, their role in the perioperative setting has scarcely been studied. Whether PC2 also relates to features of unrepaired ToF other than cyanosis-such as right ventricular pressure load, right ventricular hypertrophy or diminished flow in the pulmonary circulation-could not be established.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research found that preoperative cyanosis may affect platelet function and increase platelet aggregation 31. Furthermore, other biomarkers of collagen and other matrix metalloproteinase subtypes have been related to outcomes in congenital heart disease 32–34. However, their role in the perioperative setting has scarcely been studied.…”
Section: Discussionmentioning
confidence: 99%
“…This is same with the research by Kilic et al in Turkey showed no significant difference between the levels of MMP-9 in the age group with a value of p>0.05. [14] Research by Lee et al in Korea showed that there was no significant difference between the expression levels of MMP-9 age group, with a p value 0.820. [15] The analyses of the comparison between the levels of MMP-9 and nutritional status showed no significant difference (p value of 0.70).…”
Section: Discussionmentioning
confidence: 99%